Strategic Planning for IS/IT of XYZ Internet Service Provider Using Ward and Peppard Method - Febriyanti, Kadek Dwi; Samopa, Febriliyan; Ambarwati, Rita (Institut Teknologi Sepuluh Nopember, 2019)
PT. XYZ is one of the leading Internet service providers in East Java, Bali and Lombok. As an IT company that has the motto